Belowground and aboveground herbivory differentially affect the transcriptome in roots and shoots of maize - Ye, Wenfeng; Bustos Segura, Carlos; Degen, Thomas; Erb, Matthias; Turlings, Ted (My University, 2022)
Plants recognize and respond to feeding by herbivorous insects by upregulating their local and systemic defenses. While defense induction by aboveground herbivores has been well studied, far less is known about local and systemic defense responses against attacks by belowground herbivores. Here, we investigated and compared the responses of the maize transcriptome to belowground and aboveground mechanical damage and infestation by two well-adapted herbivores: the soil-dwelling western corn rootworm Diabrotica virgifera virgifera (Coleoptera: Chrysomelidae) and the leaf- chewing fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae). In responses to both herbivores, maize plants were found to alter local transcription of genes involved in phytohormone signaling, primary and secondary metabolism. Induction by real herbivore damage was considerably stronger and modified the expression of more genes than mechanical damage. Feeding by the corn rootworm had a strong impact on the shoot transcriptome, including the activation of genes involved in defense and development. By contrast, feeding by the fall armyworm induced only few transcriptional changes in the roots. In conclusion, feeding by a leaf chewer and a root feeder differentially affects the local and systemic defense of maize plants. Besides revealing clear differences in how maize plants respond to feeding by these specialized herbivores, this study reveals several novel genes that may play key roles in plant–insect interactions and thus sets the stage for in depth research into the mechanism that can be exploited for improved crop protection.
Keywords: belowground and aboveground defense interactions; Diabrotica virgifera; phytohormones; Spodoptera frugiperda; transcriptome; Zea mays